2021
DOI: 10.1002/ajh.26299
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous T‐cell lymphomas: 2021 update on diagnosis, risk‐stratification, and management

Abstract: Disease overview: Cutaneous T-cell lymphomas are a heterogenous group of T-cell neoplasms involving the skin, the majority of which may be classified as Mycosis Fungoides (MF) or Sézary Syndrome (SS). Diagnosis: The diagnosis of MF or SS requires the integration of clinical and histopathologic data.Risk-adapted therapy: TNMB (tumor, node, metastasis, blood) staging remains the most important prognostic factor in MF/SS and forms the basis for a "risk-adapted," multi-disciplinary approach to treatment. For patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 270 publications
(580 reference statements)
0
32
0
1
Order By: Relevance
“…Primary cutaneous lymphomas are non‐Hodgkin lymphomas without extracutaneous disease at the time of diagnosis and are typically indolent. 1 , 2 CD30 positivity may suggest the potential for large cell transformation and progression. 3 Brentuximab vedotin (BV) is an anti‐CD30 antibody‐drug conjugate newly approved to treat CD30+ cutaneous lymphomas.…”
Section: Figurementioning
confidence: 99%
“…Primary cutaneous lymphomas are non‐Hodgkin lymphomas without extracutaneous disease at the time of diagnosis and are typically indolent. 1 , 2 CD30 positivity may suggest the potential for large cell transformation and progression. 3 Brentuximab vedotin (BV) is an anti‐CD30 antibody‐drug conjugate newly approved to treat CD30+ cutaneous lymphomas.…”
Section: Figurementioning
confidence: 99%
“…113 Patients with Sézary syndrome (SS) are predisposed to secondary malignancies. 115,116 SS is a leukemic form of epidermotropic cutaneous T-cell lymphoma characterized by pruritus and squamous erythroderma. Among patients with SS, 27% develop a secondary malignancy.…”
Section: Predisposing Factorsmentioning
confidence: 99%
“…Antigen-specific T cells overexpressing CD5 reportedly persist better as memory T cells after peripheral activation [ 93 ]. The loss of CD5 is sometimes seen in the advanced stages of MF [ 94 ]. However, the expression of CD5 is also reported to be higher in the malignant T cells of SS compared to the benign T cells [ 89 ].…”
Section: Distinguishment Of Malignant and Benign T Cells In Ctclmentioning
confidence: 99%
“…CTCL is treated with various modalities, including topical therapies, ultraviolet (UV) therapies, radiation therapies, and systemic therapies [ 94 ]. It has been reported that the cytokine profile of benign T cells is significantly changed before and after effective treatments.…”
Section: Benign T Cells In Ctclmentioning
confidence: 99%